The Impact of FOMO Culture and Digital Social Pressure on the Ethical Behavior of Young Consumers Toward Local Products - Rahman, Priyanggo Karunia (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The rise of social media and digital culture has reshaped how young consumers make moral decisions, particularly in purchasing local products. The phenomenon of Fear of Missing Out (FOMO) has emerged as a psychological driver that fuels impulsive and symbolic consumption among Generation Z. This study aims to analyse the extent to which digital social pressure and FOMO culture influence the ethical behaviour of young consumers when buying local products in the era of algorithmic capitalism. A qualitative conceptual approach was employed through a systematic literature review of relevant studies published between 2020 and 2025. The analysis followed a deductive–thematic process to explore the relationships among intrinsic moral motivation, digital social pressure, and ethical fading in consumer behaviour. The findings reveal that while ethical awareness toward local products is increasing, social pressure and FOMO culture tend to shift consumers’ moral orientation from intrinsic values to extrinsic motivations based on trends and social validation. This phenomenon amplifies the attitude-behaviour gap and indicates a transformation of morality from personal reflection to algorithmic conformity. The study concludes that ethical consumer behaviour in the digital age must be understood as the outcome of an interaction between individual values, technological design, and social media pressure. It recommends enhancing digital moral literacy and encouraging local businesses to build authentic ethical narratives so that young consumers’ decisions remain grounded in moral awareness rather than transient digital trends.